2021
DOI: 10.1186/s12920-021-01009-7
|View full text |Cite
|
Sign up to set email alerts
|

New familial cases of karyomegalic interstitial nephritis with mutations in the FAN1 gene

Abstract: Background Karyomegalic interstitial nephritis (KIN) is a rare disease entity first described by Burry in 1974. The term KIN was introduced by Mihatsch et al. in 1979. KIN is characterized by chronic tubulointerstitial nephritis associated with enlarged tubular epithelial cell nuclei, which leads to a progressive decline of renal function. The prevalence of this disease is less than 1% of all biopsies, and its pathogenesis is unclear. KIN results from mutations in FAN1 (FANCD2/FANCI-Associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The short stature, the striking leanness without any signs of a malignant disease, the café au lait color of the skin, the facial freckles, the hawk-like appearance of the nose, and mental capacity at the lower border of average or even below average were obvious features in patients B, C, D, and E. These abnormalities have not been discussed in earlier publications on KIN [ 17 , 18 , 27 , 28 , 29 ]. However, a focused review of the reports by us revealed a history of facial rash in one patient [ 20 ], atrophy and retraction of the left and right side of the nose in two patients [ 12 ], epilepsy in two patients [ 2 , 18 ], multiple sclerosis in one patient [ 8 ], and depression and emaciation in one patient [ 9 ]. It is unclear whether these abnormalities were mere coincidences or were true manifestations of FAN1 -related systemic disease.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The short stature, the striking leanness without any signs of a malignant disease, the café au lait color of the skin, the facial freckles, the hawk-like appearance of the nose, and mental capacity at the lower border of average or even below average were obvious features in patients B, C, D, and E. These abnormalities have not been discussed in earlier publications on KIN [ 17 , 18 , 27 , 28 , 29 ]. However, a focused review of the reports by us revealed a history of facial rash in one patient [ 20 ], atrophy and retraction of the left and right side of the nose in two patients [ 12 ], epilepsy in two patients [ 2 , 18 ], multiple sclerosis in one patient [ 8 ], and depression and emaciation in one patient [ 9 ]. It is unclear whether these abnormalities were mere coincidences or were true manifestations of FAN1 -related systemic disease.…”
Section: Discussionmentioning
confidence: 86%
“…Respiratory tract (mostly upper) infections and/or abnormal liver function tests in about half of the patients completed the clinical phenotype. The immune responses even without a history of infections seemed to be impaired in KIN patients [ 18 ] because when kidney transplantation was chosen to treat end-stage renal disease, fatal infectious episodes were commonly observed besides the conventional dosage of maintenance immunosuppressive therapy [ 2 , 3 , 8 ]. The liver biopsy findings, except for the occasional presence of karyomegaly, were either normal, or non-specific or intrahepatic cholestasis of unknown etiology was found [ 4 , 5 , 9 , 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A familial clustering of disease and increased frequency of human leukocyte antigen (HLA)-A9 and HLA-B35 with genetic defects on chromosome 6 were reported [ 2 , 11 ]. In addition, KIN has been linked to mutations of the Fanconi anemia associated nuclease 1 (FAN1) gene, which is responsible for DNA repair processes [ 11 13 ]. Unlike other FAN gene mutations, the FAN1 gene mutation is not associated with Fanconi anemia, risk of malignancy, or developmental anomalies, as the gene is predominant in renal, hepatic, and neuronal tissues [ 12 ].…”
Section: Discussionmentioning
confidence: 99%